EXPERIMENTAL SOUND LEVEL ANALYSIS FOR MOTORCYCLE APPLICATION (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Exhaust noise created by the engines is important noise pollution to the environment. Exhaust systems are required to attenuate noise meeting required dB levels and sound quality, emissions based on environment norms. Hence this is become an important area for research and development. Mufflers are important part of engine system and used in exhaust system to minimize sound transmissions caused by exhaust gases. Design of muffler is a complex function that affects noise characteristics, emission and fuel efficiency of engine. Thus muffler design becomes more and more important for noise reduction. This research deals with a practical approach to design, develop reactive muffler for exhaust system, which will give advantages over the conventional method with shorten product development cycle time and validation.